HUBUNGAN AKUNTABILITAS, TRANSPARANSI, DAN KOMPETENSI SUMBER DAYA MANUSIA DENGAN KUALITAS LAPORAN KEUANGAN UMKM DI KECAMATAN PRAMBON KABUPATEN NGANJUK TAHUN 2024 - Sintya Gadis Sherly; Hestin Sri Widiawati; Erna Puspita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the relatively low quality of financial statements among some Micro, Small, and Medium Enterprises (MSMEs), which is attributed to the suboptimal implementation of accountability, transparency, and human resource competence in business financial management. This study aims to analyze the effects of accountability, transparency, and human resource competence on the quality of MSME financial statements in Prambon District, Nganjuk Regency, in 2024. A quantitative approach with a survey method was employed in this research. The population consisted of 1,194 active MSMEs in Prambon District. The sample was determined using a simple random sampling technique and the Slovin formula with a 10% margin of error, resulting in 92 respondents. Data were collected through questionnaires using a Likert scale and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination (R²), t-tests, and F-tests with the assistance of SPSS software. The results indicate that accountability and transparency have a positive and significant effect on the quality of MSME financial statements, while human resource competence has a positive but insignificant effect. Simultaneously, accountability, transparency, and human resource competence significantly affect the quality of MSME financial statements. The Adjusted R Square value of 0.688 indicates that 68.8% of the variation in financial statement quality can be explained by these three variables, while the remaining 31.2% is influenced by other factors outside the scope of this study.